1998
DOI: 10.1002/(sici)1097-4652(199809)176:3<545::aid-jcp11>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-catalyzed calponin phosphorylation in swine carotid arterial homogenate

Abstract: Calponin, a thin filament-associated protein, inhibits actin-activated myosin ATPase activity, and this inhibition is reversed by phosphorylation. Calponin phosphorylation by protein kinase C and Ca2+/calmodulin-dependent protein kinase II has been shown in purified protein systems but has been difficult to demonstrate in more physiological preparations. We have previously shown that calponin is phosphorylated in a cell-free homogenate of swine carotid artery. The goal of this study was to determine whether pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Calponin is also a well-established in vitro substrate for PKC as well as a possible in vivo substrate for PKC (56). Rokolya et al (42) demonstrated that the physiological kinase for calponin phosphorylation is PKC. Studies (32) from other laboratories have indicated that PKC activity is related to its subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…Calponin is also a well-established in vitro substrate for PKC as well as a possible in vivo substrate for PKC (56). Rokolya et al (42) demonstrated that the physiological kinase for calponin phosphorylation is PKC. Studies (32) from other laboratories have indicated that PKC activity is related to its subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the use of the protein kinase C substrate peptide, MBP 4-14 , in the determination of protein kinase C activity in a homogenate of the swine carotid artery (Rokolya et al, 1998). In our present study, we used MBP 4-14 to determine if protein kinase C is activated during Ca 2ϩ stimulation of the Triton X-100 detergent-skinned carotid arterial strip.…”
Section: Ca 2؉ -Dependent Activation Of Protein Kinase Cmentioning
confidence: 96%